'I do not share it with others. No, it's for me, it's my care': On sharing of patient accessible electronic health records. (December 2020) - Nurgalieva, Leysan; Cajander, Åsa; Moll, Jonas; Åhlfeldt, Rose-Mharie; Huvila, Isto; Marchese, Maurizio
This study explores patients' perspectives on sharing their personal health data, which is traditionally shared through discussions with peers and relatives. However, other possibilities for sharing have emerged through the introduction of online services such as Patient Accessible Electronic Health Records (PAEHR). In this article, we investigate strategies that patients adopt in sharing their PAEHR. Data were collected through a survey with 2587 patients and through 15 semi-structured interviews with cancer patients. Results show that surprisingly few patients share their information, and that older patients and patients with lower educational levels share more frequently. A large majority of patients trust the security of the system when sharing despite the high sensitivity of health information. Finally, we discuss the design implications addressing identified problems when sharing PAEHR, as well as security and privacy issues connected to sharing.